2016
DOI: 10.1186/s40066-016-0061-9
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal analysis of the impact of climate, cropping intensity and means of irrigation: an assessment on rice yield determinants in Bangladesh

Abstract: Background: Rice (Oryza sativa) is the most important staple food for almost half of the global population. Improvement of rice yield is of global concern and is influenced by a wide variety of regional factors including climate and agricultural management. This research addresses the need to understand the relative influence of these factors and develop geographically explicit determinants of rice yield across Bangladesh. The specific objectives of this study were (a) to assess spatial and temporal variation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…A correction was made for harvested area versus physical area. In China, for example this ratio of physical area to harvested area is around 0.6 due to multiple and triple cropping (Frolking et al, 2002), in Bangladesh 0.67 in 1980 CE and 0.55 in 2010 CE (Ara et al, 2016), in Vietnam 0.63 (range 1.25-0.48) (Wiens, 1998), and India 0.71-0.73 (GYGA, 2017;Kalaiselvi and Sundar, 2011). The 0.6 ratio was also applied to other Asian rice-producing countries; the rest of the world is assumed to have a ratio of 1.0.…”
Section: Ricementioning
confidence: 99%
“…A correction was made for harvested area versus physical area. In China, for example this ratio of physical area to harvested area is around 0.6 due to multiple and triple cropping (Frolking et al, 2002), in Bangladesh 0.67 in 1980 CE and 0.55 in 2010 CE (Ara et al, 2016), in Vietnam 0.63 (range 1.25-0.48) (Wiens, 1998), and India 0.71-0.73 (GYGA, 2017;Kalaiselvi and Sundar, 2011). The 0.6 ratio was also applied to other Asian rice-producing countries; the rest of the world is assumed to have a ratio of 1.0.…”
Section: Ricementioning
confidence: 99%
“…There is already evidence that a shortening of the rainy season, or heavy rainfall, high temperatures, cold waves, or more frequent dry spells can all influence rice yields locally in certain districts in Bangladesh [37,38]. Disasters [35,36], regional management [1,39], and local microclimatic conditions [37] have become important indicators of change, which need further local investigation.…”
Section: Data Limitations Uncertainties and Future Researchmentioning
confidence: 99%
“…Rice has become a primary concern for national food security in Bangladesh [1][2][3]. Climate change may influence rice food security in many parts of the world including Bangladesh [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Choudhury and Khan (2015) showed that the Aman rice yield has gradually increased by almost 3 fold from 1972 to 2014. Increasing temperature and variable rainfall levels along with severe and frequent floods, droughts and cyclones adversely affect agricultural production and place Bangladesh's food security at risk (Ara et al, 2016;Karim, 2012;Zakaria et al, 2014). The aim of this paper is to assess the impact of climatic parameters on Aman rice production in Rangpur District, a district from north-western region of Bangladesh.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%